Issues Arising from the Creation of Special Economic Zone in Southern Thailand: A Scoping Step of Rapid Health Impact Assessment (Medico Legal Update, 2021)
Background: Special Economic Zone (SEZ) policy of Thai government aimed to promote the economyin bordered provinces. Its establishment may cause concerns and impacts on communities. This articleexplores those issues arising from SEZ establishment in Southern Thailand.Method: The scoping step of rapid health impact assessment process was applied using documentaryresearch combined with qualitative descriptive approaches, including focus group discussions, interviews,and brainstorming. Data were collected from seventy participants, comprising government officials, localgovernment officials, community leaders, public health volunteers, members of local organizations, andlocal residents. Content analysis was used to analyze the data.Conclusion: The most important issues were found in four aspects—economic, social, environmental, andhealth. The economic aspect involved higher income and more employment opportunities, while for theenvironmental aspect, the issues were related to waste management and water pollution. The social issuescomprised the build-up of traffic and the influx of migrant workers. The health issues were emerging/reemerging infectious diseases, particularly from migrant workers and the insufficiency of health services. Asa result, a rapid health impact assessment should be carried out based on these issues. It should be taken intoconsideration by local officials responsible for developing and regulating the SEZ.